Effect of neuroticism on Chinese athletes’ vigor: serial mediating roles of pre-competition anxiety and mind wandering - Li, Jieling; Li, Chuangye; Tian, Bao (Frontiers in Public Health, 2024)
IntroductionVigor plays an important role in mental health, and it is closely related to sporting performance. Neuroticism can affect individual vigor, but its internal mechanism remains unclear. This study aims to examine the relationship between neuroticism and vigor, and the role of anxiety and mind wandering between the two.MethodsA total of 591 athletes completed questionnaires on neuroticism, pre-competition anxiety, mind wandering and vigor. The survey data were tested for common method biases, Pearson’s correlation, and structural equation model via SPSS 25.0 and Mplus 7.0.ResultsResults showed that neuroticism had a predictive effect on athletes’ vigor 4 (β = −0.511, p < 0.001). Pre-competition anxiety (β = −0.056, BC 95% CI = [−0.091, −0.028]) and mind wandering (β = −0.030, BC 95% CI = [−0.054, −0.014]) mediate neuroticism effects on vigor separately. There was a significant serial mediation effect from “neuroticism→Pre-competition anxiety→mind wandering→energy” (β = −0.010, BC 95% CI = [−0.023, −0.002]).DiscussionThis study provides a reference for the systematic investigation of the relationship between neuroticism and vigor, and specific intervention methods for ensuring athletes’ vigor and improving sports performance.